Persaingan Tidak Seimbang Akibat Inovasi Digital di Pasar Tradisional: Analisis Mekanisme Pasar Menurut Abu Yusuf - Abdillah Qadry Azizi; Mugiyati Mugiyati (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze market mechanisms from the perspective of Abu Yusuf's thinking and their relevance to the phenomenon of digital innovation at Pasar Kembang Surabaya. The observed phenomenon is the emergence of a bread seller who utilizes social media, specifically TikTok live, to sell his products directly to consumers, which creates market inequality and decreases income for traders. This study uses a qualitative field approach through interviews with traders, traders, and market managers, as well as a literature review of Abu Yusuf's thinking regarding market mechanisms, prices, and distribution justice. The results show that digital innovation disrupts the existing traditional market structure. In Abu Yusuf's view, market mechanisms must operate based on open market principles, with the state overseeing to prevent inequality that disproportionately harms certain parties. Furthermore, according to Abu Yusuf, this phenomenon does not constitute a situation or event that harms others because it is a sales innovation and lacks many regulations. This phenomenon demonstrates the need for inclusive technological adaptation to ensure that small traders are not left behind and to create healthy competition.